Measuring the effects of differentially intense information on political opinions - Claudia Zucca (PLoS ONE, 2025)
The field of public opinion has already extensively addressed how political opinions form and change. However, we still need to find out why some information flows affect opinions more effectively than others. The concept of intensity is employed to assess the differential penetrating power attributed to different political information flows. A measure of the intensity of information flows is presented and tested on British respondents with a survey experiment that employs vignettes with information flows concerning the former British Conservative Prime Minister Theresa May. This study finds that the measure of intensity is able to identify information flows that have a larger probability of affecting opinions. Information flows characterised by higher intensity are more likely than information flows characterised by low intensity to influence opinion formation about the former British leader. Still, respondents’ pre-existing political awareness and predispositions condition the effect of information flow intensity in agreement with established theories in public opinion. Different political awareness and predispositions are associated with different reactions to the intensity of information flows. Finally, the study finds that effects can be observed only if the information flow is intense enough, independent of the respondents’ attitudes.